Instructional Leadership in School Literacy: A Systematic Literature Review Based on Scopus and Google Scholar Data (2020–2025) - Hariyani Prasetyaningtyas; Mohammad Sofwan Effendi; Sugiarto Sugiarto; Kamaludin Kamaludin (Journal of Educational Sciences, 2026)
Research on instructional leadership and school literacy has increased significantly; however, prior studies often examine leadership practices, collaboration, or literacy outcomes separately, resulting in limited integrative understanding of how these elements function as a coherent school-wide system. This study aims to systematically analyze how instructional leadership contributes to strengthening primary school literacy through organizational, collaborative, and instructional processes. A Systematic Literature Review was conducted following the PRISMA 2020 protocol. Forty-five open-access studies published between 2020 and 2025 were retrieved from Scopus and Google Scholar. The data were analyzed using thematic synthesis and bibliometric mapping with VOSviewer to identify dominant patterns, research clusters, and conceptual relationships. The findings indicate that instructional leadership positions literacy as a strategic school agenda through policy direction and supervision, effective implementation depends on structured collaboration among principals, teachers, and librarians, and systematic literacy management is consistently associated with improved student academic achievement. This study concludes that school literacy operates as a collaborative instructional ecosystem governed by leadership processes, offering a conceptual contribution to instructional leadership theory and guidance for coherent literacy policy and practice.